TINJAUAN I’JAZ TASYRI’ KHAMAR DALAM AL-QUR’AN - Muhammad Syukri (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
The Qur'an is a guidance book for mankind of all ages, which has an extraordinary aspect of magnificence. It's supported by no human being capable of confronting it. The purpose of this article is to discuss further how the editing of the Qur'an about khamar and the beauty of taxyri' contained in it, to deepen th e knowledge of the problem of khamar in the Quran and to investigate how the scientific beauty of the ban khamar exists.